2020
DOI: 10.1002/jbt.22450
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the protective and therapeutic effect of melatonin against thioacetamide‐induced acute liver damage

Abstract: Acute or chronic damage to the liver may occur through alcohol, drugs, viruses, genetic disorders, and toxicity. In this study, we planned to investigate the protective and therapeutic effects of melatonin (Mel) by causing damage to the liver with thioacetamide (TAA). Thirty‐five rats were used. Group I: control group (seven pieces), group II: Mel group (seven pieces) the single dose on the first day of the experiment was 10 mg/kg, group III: TAA (seven pieces) 300 mg/kg with 24‐hour intervals, two doses, grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 56 publications
0
7
0
1
Order By: Relevance
“…Sections were stained with Hematoxylin‐Eosin (H&E), photographs were taken with an light microscope (Olympus BX51, Center Valley, PA). [ 14 ]…”
Section: Methodsmentioning
confidence: 99%
“…Sections were stained with Hematoxylin‐Eosin (H&E), photographs were taken with an light microscope (Olympus BX51, Center Valley, PA). [ 14 ]…”
Section: Methodsmentioning
confidence: 99%
“…However, co-treatment of melatonin and cisplatin, rats exhibited a positive PAS and increased PAS optical density in zona pellucida and oocyte. The previous study showed that melatonin, although by a small amount, corrected thioacetamide, it caused depletion of liver glycogen storage according to PAS staining [54]. The distribution of glycogen density was found to be increased in the bisphenol A and melatonin compared to the bisphenol-A only treated rats [55].…”
Section: Discussionmentioning
confidence: 81%
“…Yine CCl4 ile yapılan çalışmalarda CCl4'ün kaspaz enzim sistemini aktive ederek apoptozu arttırdığı ve böylece doku hasarına yol açtığı bildirilmiştir (8,25). Başka bir maddeyle karaciğer hasarının indüklendiği bir çalışmada kaspaz-3 pozitif hepatositlerin sayısı hasar oluşturulan grupta yüksek bulunmuştur (26). Akciğer dokusunda yapılan çalışmaları incelediğimizde ise, CCl4 ile oluşturulan akciğer hasarında kaspaz-3 enzim aktivitesi diğer gruplardan yüksek bulunmuştur (8).…”
Section: Discussionunclassified